Heterophile binding of human antibodies to glycoproteins of retroviruses. - Cardoso, E. A. (Nature Publishing Group, 1981)
The binding of human immunoglobulin to Type C viruses has been analysed by radioimmunoassay. The assay is a double-antibody, solid-phase RIA, which has been optimized and calibrated using rabbit and human anti-MuLV sera. It detects varying concentrations of IgG binding to HL-23-V-1, a human Type C virus isolate, in all of a large number of human sera tested. As judged by inhibition with nonspecific glycoproteins, heterophile antigens and pure saccharides, this binding is to the glycoside moiety of the virus-envelope glycoproteins, in agreement with other recent reports. Nonspecific binding of this type stringently restricts the interpretation which can be placed on these and earlier data in man concerning antibodies to Type C viruses. It does not however exclude the possibility that Type C viruses do occur in man and do elicit antibody therein. IMAGES: